The Implementasi Program Pembelajaran Moderasi Beragama Melalui Penanaman Akidah Akhlak di MAN 1 Kota Bandung - M. Noval Asgaf; Erhamwilda (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research is titled "Implementation of Religious Moderation Learning Program Through Inculcation of Islamic Theology and Ethics at State Islamic Senior High School (MAN) 1 Bandung City". The main focus of the research is to analyze how religious moderation values are integrated into the teaching of Islamic theology and ethics to shape moderate religious understanding and attitudes among students. The research method used is qualitative descriptive. The qualitative method is commonly used in research processes to produce data presented in the form of spoken or written words from observable sources. With this method, the author obtains data through interviews, observation, and documentation study. From these stages, the author reveals the results of the interviews, quoting them to gain in-depth information and capture existing realities. The research subjects include the vice principal of curriculum, Islamic theology and ethics teachers, Islamic education teachers, and students of MAN 1 Bandung City. The research results show that the implementation of the religious moderation learning program through the inculcation of Islamic theology and ethics is carried out through: 1) Planning of the religious moderation learning program; 2) Implementation of the religious moderation program in both classrooms and dormitories; 3) Evaluation of the religious moderation learning program. With this implementation, it can be concluded that there is an improvement in students' application of religious moderation values in daily life, both within the school and dormitory environments. The challenges faced in this implementation include the lack of measurement tools to evaluate existing learning and the lack of motivation among students to actively participate in classroom learning. Abstrak. Penelitian ini dengan judul Implementasi Program Pembelajaran Moderasi Beragama melalui Penanaman Akidah Akhlak di Madrasah Aliyah Negeri (MAN) 1 Kota Bandung. Fokus utama penelitian adalah menganalisis bagaimana nilai-nilai moderasi beragama diintegrasikan ke dalam pembelajaran akidah akhlak untuk membentuk pemahaman dan sikap keagamaan yang moderat pada siswa. Metode penelitian yang digunakan adalah kualitatif deskriptif. Metode kualitatif merupakan metode yang biasa digunakan dalam proses penelitian dengan menghasilkan data yang disajikan dalam bentuk kata-kata secara lisan atau tulian dari narasumber yang dapat diamai. Adapun dengan metode ini penulis mendapatkan data melalui tahapan wawancara, observasi, dan studi dokumentasi. Selanjutnya dari hasil tahapan tersebut penulis mengungkapkan hasil dari wawancara tersebut dikutip untuk mendapatkan informasi yang mendalam dan mencakup realita yang ada. Adapun subjek penelitian meliputi wakasek kurikulum, guru akidah akhlak, guru PAI dan siswa MAN 1 Kota Bandung. Hasil penelitian menunjukkan bahwa implementasi program pembelajaran moderasi beragama melalui penanaman akidah akhlak dilakukan dengan: 1) Perencanaan program pembelajaran moderasi beragama; 2) Pelaksanaan program moderasi beragama antara kelas dan asrama; 3) Evaluasi program pembelajaran moderasi beragama. Dengan adanya penerapan tersebut dapat disimpulkan bahwasaanya terjadinya peningkatan siswa dalam menerapkan nilai-nilai moderasi beragama dalam kehidupan sehari-hari baik itu di lingkup madrasah ataupun dalam lingkup asrama. Adapun tantangan yang dihadapi melalui implementasi ini yaitu kurangnya alat ukur dalam mengevaluasi pembelajaran yang ada dan kurangnya motivasi pada siswa untuk aktif dalam pembelajaran ketika di kelas.